2022
DOI: 10.3390/nu14081547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Warning Labels on Consumer Motivation and Intention to Avoid Consuming Processed Foods

Abstract: Nutritional warnings (NWs) as a front-of-package label were implemented as a public policy aiding consumers with recognizing processed foods with high levels of critical nutrients (sodium, saturated fats, carbohydrates, and calories). However, in spite of this tool being well positioned in consumer decision making, there is little extant knowledge about the relationship between the message sent by NW, nutritional knowledge, consumer motivation, and the intention to avoid consuming processed foods. To understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In another study by Cristian Adasme-Berríos et al (2002), it was reported that Nutrition Warnings (NWs) increase the avoidance of processed foods [ 9 ]. The message provided by NWs had a mediating effect between the intention to avoid processed food and eating motivation, but showed no such effect on nutritional knowledge.…”
mentioning
confidence: 99%
“…In another study by Cristian Adasme-Berríos et al (2002), it was reported that Nutrition Warnings (NWs) increase the avoidance of processed foods [ 9 ]. The message provided by NWs had a mediating effect between the intention to avoid processed food and eating motivation, but showed no such effect on nutritional knowledge.…”
mentioning
confidence: 99%